BENDA ASTRONOMI DALAM AL-QURAN DARI PERSPEKTIF SAINS - Hasan, Muhammad (TEOLOGIA, 2015)
Abstract: The objects in the sky in an astronomical perspective is very much the type and amount, but in the perspective of The Quran consists only of the sun, moon, and stars. The Quran gives cues and clues about the movement of the heavenly bodies. Sky objects in the perspective of the Koran already set his destiny, and had been subdued, so consistently and definitely outstanding. According to The Quran cue each celestial bodies, circulation and no silent, including the sun are also outstanding. In the circulation of the month, has its own characteristics, because only months in circulation set manzilah-manzilah, so the moon when seen from Earth show different form, sometimes the perfect (full moon), and sometimes show an imperfect form. Thus, it can be well known, when the month of the date of 1,2,3, and so on, so that people can practice their religion is based on the moon trip. Abstrak: Benda-benda di langit dalam perspektif astronomi sangat banyak jenis dan jumlahnya, namun dalam perspektif al-Quran hanya terdiri dari matahari, bulan, dan bintang. Al-Quran  memberikan  isyarat  dan  petunjuk  mengenai  pergerakan benda-benda  langit tersebut. Benda-benda langit  dalam  perspektif  al-Quran  sudah  ditetapkan  takdir-Nya,  dan telah  ditundukkan, sehingga beredar  secara  konsisten  dan  pasti. Menurut isyarat al-Quran masing-masing  benda  langit,  beredar  dan  tidak  ada  yang  diam, termasuk matahari juga beredar. Dalam peredaran bulan, memiliki ciri tersendiri, karena  hanya bulan  yang dalam  peredarannya  ditetapkan  manzilah-manzilah,  sehingga  bulan  ketika  dilihat  dari  bumi  menunjukkan  wujud yang berbeda-beda, kadang  sempurna (bulan  purnama),   dan terkadang menunjuk-kan  wujud yang    tidak  sempurna. Dengan  demikian, dapat  dikenal  dengan  baik,  kapan bulan  tanggal  1,2,3, dan  seterusnya,  sehingga  manusia dapat  melaksanakan  ibadah berdasarkan  perjalanan  bulan  tersebut. Keywords:  matahari, bulan, bintang, al-Quran, astronomi